What is the differential diagnosis for an incidentally discovered adrenal mass?. Issue 4 (April 2017) - Hobart, Keeley; Ireland, Jade A.; Haynes, Jamie
Abstract : EVIDENCE‐BASED ANSWER : In patients with incidentally discovered adrenal masses on imaging and no history of malignancy or signs and symptoms of adrenal disease, the differential diagnosis includes nonsecreting adenomas (75%‐85%), cortisolsecreting adenomas (9%), and a number of uncommon causes (<5% total) such as pheochromocytomas, aldosteronomas, adrenal cortical carcinomas, myelolipomas, cysts, hematomas, ganglioneuromas, and metastases (SOR: C, retrospective case series).